2008
DOI: 10.1007/s00018-008-8143-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of galectin-1 with GM1 ganglioside in the course of its clathrin- and raft-dependent endocytosis

Abstract: Mammalian galectin-1 (Gal-1), a beta-galactoside-binding lectin has a prominent role in regulating cell adhesion, cell growth and immune responses. Downregulation of these biological functions may occur via internalization of Gal-1. In the present study we have investigated the mechanism and possible mediator(s) of Gal-1 endocytosis. We show that internalization occurs at a temperature higher than 22 degrees C in an energy dependent fashion. After one hour incubation Gal-1 localizes in the Golgi system within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
3
35
0
1
Order By: Relevance
“…A recent study in nonendothelial cells indicated that galectin-1 can be actively endocytosed. The uptake of galectin-1 was carbohydrate dependent and might involve GM1, a galectin-1-binding glycosphingolipid (36). Further analysis revealed that the internalization was facilitated by multiple routes (i.e., lipid-raft dependent and clathrin-mediated endocytosis; ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in nonendothelial cells indicated that galectin-1 can be actively endocytosed. The uptake of galectin-1 was carbohydrate dependent and might involve GM1, a galectin-1-binding glycosphingolipid (36). Further analysis revealed that the internalization was facilitated by multiple routes (i.e., lipid-raft dependent and clathrin-mediated endocytosis; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis revealed that the internalization was facilitated by multiple routes (i.e., lipid-raft dependent and clathrin-mediated endocytosis; ref. 36). Additional studies are needed to determine whether such mechanisms are also involved in endothelial uptake of galectin-1.…”
Section: Discussionmentioning
confidence: 99%
“…The Gal-1 ligand ganglioside GM1 has recently been identified as important for endocytosis of Gal-1 in Jurkat cells, a process mediated by clathrin and lipid raft-dependent mechanisms, although the reason for internalisation remains to be established (Fajka-Boja et al 2008). Gal-1 binds to a number of leukocyte cell surface molecules including CD4, CD7, SPN and PTPRC (Perillo et al 1995, Hernandez & Baum 2002, Stillman et al 2006.…”
Section: Actions Of Exogenous Galectin-9mentioning
confidence: 99%
“…Extracellular functions: Gal-1 may be secreted by an unconventional fashion [13,14]. Its extracellular functions are many-fold and have been extensively studied [15,16].…”
Section: Structure Of Galectin-1mentioning
confidence: 99%
“…Extracellular Gal-1 causes apoptosis of activated T-cells, a major immunoregulatory function of the lectin. Although a number of T-cell Gal-1-binding structure has been identified, including CD45 [17], CD7 [18], GM1 ganglioside [14,19], the exact receptor mediating Gal-1's triggered apoptosis remains unknown. Gal-1 driven apoptotic signalling is not dependent on the Fas/FasL pathway according to studies on a Fas-resistant T-cell line and lpr mice [20,21].…”
Section: Structure Of Galectin-1mentioning
confidence: 99%